The potential for cleaner fish‐driven evolution in the salmon louse Lepeophtheirus salmonis: Genetic or environmental control of pigmentation?. Issue 12 (16th May 2021) - Hamre, Lars Are; Oldham, Tina; Oppedal, Frode; Nilsen, Frank; Glover, Kevin Alan
Abstract: The parasitic salmon louse represents one of the biggest challenges to environmentally sustainable salmonid aquaculture across the globe. This species also displays a high evolutionary potential, as demonstrated by its rapid development of resistance to delousing chemicals. In response, farms now use a range of non‐chemical delousing methods, including cleaner fish that eat lice from salmon. Anecdotal reports suggest that in regions where cleaner fish are extensively used on farms, lice have begun to appear less pigmented and therefore putatively less visible to cleaner fish. However, it remains an open question whether these observations reflect a plastic (environmental) or adaptive (genetic) response. To investigate this, we developed a pigment scoring system and conducted complimentary experiments which collectively demonstrate that, a) louse pigmentation is strongly influenced by environmental conditions, most likely light, and b) the presence of modest but significant differences in pigmentation between two strains of lice reared under identical conditions. Based on these data, we conclude that pigmentation in the salmon louse is strongly influenced by environmental conditions, yet there are also indications of underlying genetic control. Therefore, lice could display both plastic and adaptive responses to extensive cleaner fish usage where visual appearance is likely to influence survival of lice. Abstract : Recent anecdotal reports suggest that in regions where cleaner fish are extensively used on farms, lice appear less pigmented and therefore less visible to the cleaner fish. To answer whether these observations reflect a plastic (environmental) or adaptive (genetic) response, we developed a pigment scoring system and conducted complimentary experiments that demonstrate that lice pigmentation is strongly influenced by environmental conditions, and most likely daylight. We also detected small but significant differences in pigmentation between two strains of lice reared in the same environment, suggesting that lice may display both plastic and adaptive responses to extensive cleaner fish usage where the degree of pigmentation is likely to influence survival.